Fabrication of biopolyester materials by electrospinning as scaffolds for tissue engineering / Pedram Azari - Pedram, Azari (2016)
Tissue loss is one of the most important reasons for failure in all the living systems. With development of newer technologies, tissue regeneration seems to be a promising alternative to conventional surgical and organ donation methods without the problems of disease transmission and availability of donor. Preparation of biocompatible and biodegradable polymeric materials for scaffolding is an important part of tissue engineering. In this research, several biopolyester scaffolding materials have been developed based on polycaprolactone (PCL) and polyhydroxybutyrate (PHB) and their combination with medium chain length polyhydroxyalkanoates and bovine hydroxyapatite (BHA) at different weight ratios through electrospinning. The resulting materials were characterized using field emission scanning electron microscopy, fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetery, and wide-angle X-ray diffraction. To study cell-scaffold interaction, rat bone marrow derived stem cells were seeded on the scaffolds and cultured in vitro followed by carrying out cell proliferation and alkaline phosphate assays. The results showed that all the produced scaffolds are biocompatible and promote stem cell and keratocytes growth and proliferation. PCL-BHA40% and PHB-BHA10% samples showed the highest proliferation rates within 14 days. Alkaline phosphate assay showed that the combination of electrospun PHB, PCL and BHA was osteoinductive and resulted in stem cells differentiation toward Osteoblasts. The gene expression results showed that electrospun PCL promotes keratocyte growth without differentiation; the feature which is useful for drug screening applications. All the produced fulfilled the preliminary requirements of tissue engineering and can be potential candidates for more detailed in vivo studies.